Coherent dual-phase type layered oxide positive electrode material of sodium-ion battery and preparation method of coherent dual-phase type layered oxide positive electrode material
Through the common dual-phase structure of sodium ion battery positive electrode material, the problems of high cost and poor stability of the positive electrode material in sodium ion batteries are solved, high energy density and cycle stability are achieved, and large-scale production is suitable.
Patent Information
- Application Number
- CN202411131210.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-17
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-08-17
AI Technical Summary
The high cost of existing sodium ion battery cathode materials and insufficient cycle stability and energy density, limiting the performance and application of sodium ion battery.
NaxMaO2@Na0.8MbO2, a sodium ion battery layered oxide positive electrode material with a common biphasic structure, was prepared by ball milling, calcining, and sol-gel methods to construct a common biphasic layered structure, inhibiting irreversible phase change and increasing Na+ Transmission rate, the functional surface layer is used to alleviate the side reaction between the electrolyte and the material, and enhance the high reactivity of the material.
The cyclic structure stability and material energy density are significantly improved, high reversible capacity and fast charging and discharging performance are achieved, and the preparation method is simple and controllable, suitable for large-scale production.
Smart Images

Figure BDA0004997876820000041 
Figure BDA0004997876820000051 
Figure BDA0004997876820000052
Abstract
Description
Technical Field
[0001] The present invention relates to a cathode material for sodium-ion batteries. Background Art
[0002] As a key material determining battery performance and cell energy density, the cathode material accounts for up to 40% of the cost, which is a bottleneck restricting the development of high-performance sodium-ion batteries. Therefore, in order to reduce the market application cost of sodium-ion batteries, it is of great significance to design a layered cathode material with high energy density and high air stability. Summary of the Invention
[0003] The object of the present invention is to provide a layered cathode material for sodium-ion batteries, which can significantly improve the cyclic structural stability and / or material energy density.
[0004] According to one aspect of the present invention, there is provided a layered oxide cathode material for sodium-ion batteries, the structural general formula of which is Na x M a O2@Na 0.8 M b O2, where 0.2 < x < 1; 0 < a ≤ 1; 0 < b ≤ 1; where M is selected from at least one of Ni, Mn, Fe, Co, Cu, Ti, V, Cr, Mg, Zn, K, Al, Ca, Mo, Ru, Nb, Ir and Zr.
[0005] For the cathode material according to the present invention, M can be selected from at least two of Ni, Mn, Fe, Mg and Ti, and more preferably from at least two of Ni, Mn and Fe.
[0006] According to another aspect of the present invention, there is provided a preparation method of the above cathode material, comprising:
[0007] Mixing a sodium source and an M source in a stoichiometric ratio and ball-milling them evenly in an inert atmosphere to obtain a mixed powder;
[0008] Pressing the obtained mixed powder into a mold and then performing a calcination treatment, and then performing a grinding treatment to obtain Na x M a O2 powder;
[0009] Dissolving a complexing agent, a sodium source and an M source in a stoichiometric ratio in a solvent to form a mixed solution;
[0010] Mixing the obtained Na x M a O2 powder and the obtained mixed solution evenly to form a biphasic mixed solution;
[0011] Heating the obtained biphasic mixed solution first to form a sol, and then continuing to heat until it turns into a gel;
[0012] The obtained gel is vacuum dried to obtain a dual-phase powder material;
[0013] The Na x M a O2@Na 0.8 M b O2 positive electrode material.
[0014] The present invention thus realizes the construction of a coherent two-phase layered positive electrode material, wherein the coherent two-phase structure constrains the internal lattice expansion through the coherent growth of the coherent structure, thereby inhibiting the irreversible phase change; and promotes the internal Na + Migration kinetics, thereby increasing Na + transmission rate; at the same time, the constructed Na 0.8 The MO2 functional surface layer can serve as a protective layer to mitigate the side reactions between the electrolyte and the internal materials, retain the high reactivity of the internal materials, and thus provide a high reversible capacity. The preparation method of the present invention is therefore simple and controllable, and the prepared positive electrode material has long cycle stability and has broad application prospects.
[0015] According to the preparation method of the present invention, the sodium source can be selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium nitrate, sodium oxide, sodium peroxide and sodium fluoride; the M source can be selected from at least one of the oxides, carbonates, hydroxides, fluorides, nitrates and hydrated compounds thereof, acetates and hydrated compounds thereof of M.
[0016] According to the preparation method of the present invention, the ball milling time can be 1 to 5 hours, and the ball mill speed can be 400 to 800 rpm.
[0017] According to the preparation method of the present invention, in the calcination treatment after the mixed powder is pressed and molded: the calcination temperature can be 600-1000°C, the insulation time can be 2-24h, the calcination atmosphere can be selected from at least one of air, oxygen or nitrogen, and the heating rate can be 1-10°C / min.
[0018] According to the preparation method of the present invention, the complexing agent can be selected from at least one of citric acid, sodium citrate, maleic acid and glycine, preferably citric acid and sodium citrate; the sodium source can be selected from at least one of sodium acetate, sodium oxalate, sodium nitrate, sodium sulfate and sodium carbonate and hydrates thereof, preferably sodium acetate, sodium oxalate and sodium carbonate; the M source can be selected from at least one of acetate, oxalate, nitrate, sulfate and carbonate and hydrates thereof, preferably acetate, oxalate and hydrates thereof; the solvent can be selected from at least one of water, methanol, ethanol, ethylene glycol, isopropanol, propanol, N-methylpyrrolidone, N-dimethylformamide, acetone, acetonitrile and ether, preferably methanol, ethanol and ethylene glycol.
[0019] According to the preparation method of the present invention, the heating temperature for forming the sol may be 50-80°C, and the heating temperature for converting into the gel may be 100-150°C.
[0020] According to the preparation method of the present invention, the vacuum drying temperature can be 100-130°C.
[0021] According to the preparation method of the present invention, in the calcination treatment of the dual-phase powder material: the calcination temperature can be 900-1100°C, the calcination time can be 12-36h, more preferably 15-20h. The heating rate is more preferably about 5°C / min. The calcination atmosphere can be selected from air or oxygen.
[0022] The positive electrode material prepared according to the present invention is a coherent dual-phase sodium ion battery layered positive electrode material, and the morphology structure is a lamellar micron-sized particle with a particle size of about 1 to 5 μm. The present invention utilizes the special local structure of the coherent dual phase to significantly improve the cycle structure stability and material energy density.
[0023] According to another aspect of the present invention, a positive electrode for a sodium ion battery is also provided, wherein the positive electrode is prepared by coating a slurry formed from the above-mentioned layered positive electrode material, conductive carbon black and polyvinylidene fluoride binder on an aluminum foil current collector. The coating thickness of the positive electrode material can be 50 to 200 microns. The mass ratio of the layered positive electrode material, the conductive carbon black and the binder can be 7:2:1. The positive electrode active material loading can be 70 to 90% by weight, the content of the conductive carbon black can be 5 to 20% by weight, and the content of the binder can be 5 to 20% by weight.
[0024] The sodium ion battery assembled according to the present invention may include a full cell and a half cell. When used to test the electrical properties of the battery electrode material, a half cell may be used for testing. The electrode of the sodium ion battery assembled according to the present invention has a high energy density and excellent cycle stability, and can achieve rapid charge and discharge at a high current density.
[0025] The preparation process of the coherent two-phase layered positive electrode material provided by the present invention is simple and controllable, with low raw material cost and mild reaction conditions, and can realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is an X-ray powder diffraction test pattern according to Example 1 of the present invention;
[0027] Figure 2 is a scanning electron microscope test image of the powder prepared according to Example 1 of the present invention;
[0028] Figure 3 is an X-ray powder diffraction test pattern according to Example 2 of the present invention; and
[0029] Figure 4This is a scanning electron microscope test image of the powder prepared according to Example 2 of the present invention. DETAILED DESCRIPTION
[0030] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0031] Example 1
[0032] (1) Preparation of O3-NaNi 0.5 Mn 0.5 O2 layered cathode material: 10.5mmol sodium carbonate, 10mmol nickel oxide, and 5mmol manganese trioxide were mixed and placed in a ball mill, and the ball mill was transferred to a glove box and filled with Ar gas. The ball-to-material ratio was 20:1, the ball mill speed was 600rpm, and the running time was 180min. The three materials were fully mixed to obtain material A;
[0033] (2) The mixed material is pressed into a sheet and then placed in a muffle furnace for calcination at a heating rate of 5°C / min, a temperature of 800°C, and a holding time of 10 h. After cooling to room temperature, the material is ground into powder to obtain material B.
[0034] (3) 2 mmol sodium citrate, 0.805 mmol sodium oxalate, 0.33 mmol nickel acetate and 0.67 mmol manganese acetate were dissolved in ethanol to form a mixed solution C; then material B was added to the mixed solution C, stirred at 70° C. for 24 h to form a sol, and then stirred at 130° C. to form a gel;
[0035] (4) The gel material was transferred into a vacuum oven and dried at 120°C for 24 h to obtain a dual-phase powder material; the dual-phase powder material was then calcined at 1000°C for 24 h with a heating rate of 5°C / min to obtain NaNi 0.5 Mn 0.5 O2@Na 0.8 Ni 0.33 Mn 0.67 O2 cathode material (material D);
[0036] The prepared powder material D was subjected to XRD test. Figure 1 As shown, it can be found that the material is a coherent two-phase layered positive electrode material, and the microscopic morphology of the material is lamellar micron-sized particles, such as Figure 2 The prepared positive electrode material, binder and conductive agent were mixed in a ratio of 7:2:1, coated on aluminum foil with a coating thickness of 100 μm, dried in a vacuum oven at 80°C for 24 hours and then cut into pieces.
[0037] The battery was assembled in an argon atmosphere glove box. The cut electrode was used as the working electrode, the metal sodium was used as the counter electrode, the glass fiber was used as the separator, and 1M NaClO4 dissolved in EC / PC / 5% FEC solution was used as the electrolyte. The assembled battery was subjected to constant current charge and discharge tests in a blue electric test system with a current density of 50 mA g -1 The voltage range is 2-4.3 V, and the reversible capacity of the material after 20 cycles is 130 mAh g -1 .
[0038] Embodiment 2-3
[0039] The amount of raw materials added in step (3) of Example 1 was adjusted to: 4mmol sodium citrate, 1.61mmol sodium oxalate, 0.66mmol nickel acetate and 1.34mmol manganese acetate sample; 8mmol sodium citrate, 3.22mmol sodium oxalate, 1.32mmol nickel acetate and 2.68mmol manganese acetate sample, and other preparation conditions remained unchanged, and the preparation was carried out in turn as Examples 2 to 3. Table 1 shows the electrochemical properties of the layered positive electrode materials prepared in Examples 1 to 3.
[0040] Table 1: Electrochemical performance of Examples 1 to 3
[0041]
[0042]
[0043] Embodiments 4 to 7
[0044] The 10.5mmol sodium carbonate, 10mmol nickel oxide, and 5mmol manganese trioxide in step (1) of Example 1 were replaced by: 10.5mmol sodium carbonate, 8mmol nickel oxide, 5mmol manganese trioxide, and 1mmol iron trioxide; 10.5mmol sodium carbonate, 6mmol nickel oxide, 5mmol manganese trioxide, and 2mmol iron trioxide; 10.5mmol sodium carbonate, 4mmol nickel oxide, 5mmol manganese trioxide, and 3mmol iron trioxide; 10.5mmol sodium carbonate, 2mmol nickel oxide, 5mmol manganese trioxide, and 4mmol iron trioxide; other preparation conditions remained unchanged, and the preparation was performed in turn as Examples 4 to 7. Table 2 shows the electrochemical properties of the layered positive electrode materials prepared in Examples 4 to 7.
[0045] Table 2: Electrochemical performance of Examples 4 to 7
[0046]
[0047] Embodiments 8 to 10
[0048] The addition amount of 0.805 mmol sodium oxalate in step (3) of Example 1 was adjusted to 0.605 mmol, 0.705 mmol and 0.905 mmol sodium oxalate respectively; other preparation conditions remained unchanged, and the processes were carried out in turn as Examples 8 to 10. Table 3 is a comparison of the electrochemical properties of the layered positive electrode materials prepared in Examples 8 to 10.
[0049] Table 3: Electrochemical performance of Examples 8 to 10
[0050]
[0051]
[0052] Examples 11 to 13
[0053] The 2mmol sodium citrate, 0.805mmol sodium oxalate, 0.33mmol nickel acetate and 0.67mmol manganese acetate in step (3) of Example 1 were replaced by: 2mmol sodium citrate, 0.805mmol sodium oxalate, 0.22mmol nickel acetate, 0.67mmol manganese acetate and 0.11mmol iron acetate; 2mmol sodium citrate, 0.805mmol sodium oxalate, 0.11mmol nickel acetate, 0.67mmol manganese acetate and 0.22mmol iron acetate; 2mmol sodium citrate, 0.805mmol sodium oxalate, 0.33mmol nickel acetate, 0.33mmol manganese acetate and 0.33mmol iron acetate; and the above were carried out in turn as Examples 11 to 13. Table 4 is a comparison of the electrochemical properties of the layered positive electrode materials prepared in Examples 11 to 13.
[0054] Table 4: Electrochemical performance of Examples 11 to 13
[0055]
[0056] Comparative Examples 1-2
[0057] Each embodiment is a coherent dual-phase layered positive electrode, while the comparative example is a single-phase layered positive electrode. Take material B obtained after step (2) in Example 1 as comparative example 1. Dissolve 2mmol sodium citrate, 0.805mmol sodium oxalate, 0.33mmol nickel acetate and 0.67mmol manganese acetate in ethanol to form a mixed solution C; stir at 70°C for 24h to form a sol, and then stir at 130°C to form a gel; transfer the gel material into a vacuum oven and dry at 120°C for 24h to obtain a powder material; then calcine the powder material at 1000°C for 24h, and the obtained material is used as comparative example 2. Table 5 is a comparison of the electrochemical properties of the layered positive electrode materials obtained in comparative examples 1 to 2.
[0058] Table 5: Electrochemical performance of comparative examples 1 to 2
[0059]
[0060] By comparing Example 1 with Comparative Examples 1 and 2, it can be found that Example 1 having a coherent dual-phase structure has better structural stability and higher reversible capacity;
[0061] By comparing Example 1 with Examples 2 to 3, it can be found that functional surface layers of different thicknesses have different effects on material properties. When the thickness is that of Example 2 (20%), the material properties are the best.
[0062] By comparing Examples 1 to 3 with Examples 4 to 7 and 11 to 13, it can be found that the heteroelement coherent dual-phase material formed has better structural stability and reversible capacity within a certain ratio;
[0063] By comparing Example 1 with Examples 8 to 10, it can be found that the reversible capacity of the coherent dual-phase material is related to the sodium content of the outer functional surface layer.
[0064] In addition, in each embodiment, the ratio of the actual content of the sodium source to the theoretical content is between 0.8-1.1, which is in line with the proportion of the components of the prepared materials. In summary, the present invention adopts a method of constructing a functional surface layer to strengthen the internal structural stability of the layered positive electrode material and enhance the high activity of the internal material, which solves the problems of limited sodium storage capacity and poor cycle stability of the layered positive electrode material for sodium ion batteries in practical applications. Specifically, the high-activity inner core and high-stability outer shell formed by the sol-gel method as a dual-phase material have a synergistic effect on improving the energy density and cycle life; the lattice coherent growth of the local structure of the dual-phase material has a constraining effect on the internal lattice expansion, thereby inhibiting the irreversible phase change and improving the material cycle stability; the functional surface layer with fast ion channels is beneficial to Na + Migration kinetics, thereby increasing the Na + The transmission rate improves the material's rate performance.
Claims
1. A layered oxide cathode material for a sodium-ion battery, with a general structural formula of Na x M a O2@Na 0.8 M b O2, where 0.2 < x < 1; 0 < a ≤ 1; 0 < b ≤ 1; and M is selected from at least one of Ni, Mn, Fe, Co, Cu, Ti, V, Cr, Mg, Zn, K, Al, Ca, Mo, Ru, Nb, Ir, and Zr.
2. The positive electrode material according to claim 1, wherein M is selected from at least two of Ni, Mn, Fe, Mg and Ti.
3. The method for preparing the positive electrode material according to claim 1, comprising: The sodium source and the M source are mixed uniformly by ball milling in an inert atmosphere according to a stoichiometric ratio to obtain a mixed powder; The obtained mixed powder is pressed into a shape and then calcined and then ground to obtain Na x M a O2 powder; dissolving the complexing agent, the sodium source and the M source in a solvent according to a stoichiometric ratio to form a mixed solution; The obtained Na x M a The O2 powder is mixed evenly with the obtained mixed solution to form a two-phase mixed solution; The obtained two-phase mixed solution is first heated to form a sol, and then further heated until it is transformed into a gel; The obtained gel is vacuum dried to obtain a dual-phase powder material; The Na x M a O2@Na 0.8 M b O2 positive electrode material.
4. according to the preparation method described in claim 3, wherein the sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium nitrate, sodium oxide, sodium peroxide and sodium fluoride; The M source is selected from at least one of the oxide, carbonate, hydroxide, fluoride, nitrate and hydrated compound thereof, acetate and hydrated compound thereof of M.
5. The preparation method according to claim 3, wherein the ball milling time is 1 to 5 hours and the ball mill speed is 400 to 800 rpm.
6. The preparation method according to claim 3, wherein in the calcination treatment after the mixed powder is pressed and molded: the calcination temperature is 600-1000°C, the holding time is 2-24h, the calcination atmosphere is selected from at least one of air, oxygen or nitrogen, and the heating rate is 1-10°C / min.
7. The preparation method according to claim 3, wherein the complexing agent is selected from at least one of citric acid, sodium citrate, maleic acid and glycine; the sodium source is selected from at least one of sodium acetate, sodium oxalate, sodium nitrate, sodium sulfate and sodium carbonate and their hydrates; the M source is selected from at least one of acetate, oxalate, nitrate, sulfate and carbonate and their hydrates; and the solvent is selected from at least one of water, methanol, ethanol, ethylene glycol, isopropanol, propanol, N-methylpyrrolidone, N-dimethylformamide, acetone, acetonitrile and ether.
8. The preparation method according to claim 3, wherein the heating temperature for forming the sol is 50-80°C, and the heating temperature for converting into the gel is 100-150°C.
9. The preparation method according to claim 3, wherein the vacuum drying temperature is 100-130°C.
10. The preparation method according to claim 3, wherein in the calcination treatment of the dual-phase powder material: the calcination temperature is 900-1100°C, the calcination time is 12-36 hours, and the heating rate is 1-10°C / min.
Citation Information
Patent Citations
Layered positive electrode material of sodium-ion battery and preparation of layered positive electrode material
CN113644268A
Air-stable sodium ion battery composite layered oxide positive electrode material and preparation method thereof
CN116779807A
Layered oxide positive electrode material of sodium-ion battery as well as preparation method and application of layered oxide positive electrode material
CN117185365A
Positive electrode material of sodium ion battery, preparation method therefor, and sodium ion battery
WO2022105175A1
Layered oxide positive electrode material and preparation method therefor, and sodium-ion battery
WO2024031913A1
Cited By
Modified zinc-iron-manganese-based layered oxides, their preparation and use in sodium-ion batteries
CN122930850A